Model Pembangkitan Curah Hujan Dengan Korelasi Variasi Waktu Dan Tempat - Sutha Yadnya, Made; Wijayanti, Ari (Departemen Teknik Elektro, Universitas Diponegoro, 2008)
This research is about modelling the communication channel affected by the rain. The parameter of the model include the fading and polarization change from 30 GHz milimeter wave LMDS (Local Multipoint Distribution Service) propagation. The acquisition of data was getting online from Parsivel device supported by ASDO application software, and for rainfall measurement there are 3 raingauges used in 4 different locations at the area of ITS campus.Keywords: place variation, time variation, LMDS